Concrete Filled Tubular Elements Joints Investigation - Semko, Pavlo; Skliarenko, Serhii; Semko, Volodymyr (International Journal of Engineering and Technology, 2018)
The stress-strain state and the bearing capacity of the dismountable joints of concrete filled tubular elements are investigated. The methods of calculation and constructive solutions of concrete filled tubular elements with joints are analyzed. Five new types of dismountable joints are proposed. Experimental studies of concrete filled tubular elements have been carried out. It was determined that the most effective for compression was a joint with a steel coupling and for bending the most effective was a joint with longitudinal ribs. The numerical modeling algorithm is presented; results are verified using experimental tests. A method for constructing N-M boundary dependences for concrete filled tubular structures is proposed. Bearing capacity diagrams for concrete filled tubular elements and their joints have been constructed. The costs of the materials needed to perform the joint as the example of a real construction for similar loads are analyzed.Â